Interleukin-1? polymorphisms in Colombian patients with autoimmune rheumatic diseases (2004)
Interleukin-1 beta (IL-1?) exerts a range of inflammatory and immunomodulatory activities that are important in host defense and autoimmune response. The IL-1? gene, located on chromosome 2 (2q13), is polymorphic. The influence of its polymorphism on 355 patients with autoimmune rheumatic diseases was examined. To this effect, 172 patients with rheumatoid arthritis (RA), 114 with systemic lupus erythematosus (SLE), and 69 with primary Sjögren's syndrome (pSS) were studied. The control group consisted of 392 matched healthy individuals. Genotyping of IL-1? single-nucleotide polymorphisms (SNPs) at positions ?511 (C/T) and +3953 (C/T) was performed by the polymerase chain reaction-restriction fragment length polymorphism technique. In addition, levels of IL-1? were measured by immunoassay in supernatants of lipopolysaccharide (LPS)-stimulated and nonstimulated peripheral blood monocytes (PBM) obtained from 19 homozygous individuals for the three most common IL-1? likely haplotypes, all belonging to the control group. Allele+3953T was protective for SLE (odds ratio (OR)=0.57, 95% confidence intervals (CI)=0.34–0.88, P=0.01) as was the haplotype ?511C+3953T (OR=0.43, 95%CI=0.25–0.74, pc=0.006). The latter was associated with a lower LPS-stimulated-PBM IL-1? secretion. Results suggest that IL-1? polymorphism influences the susceptibility to acquire SLE in our population. The protective association might be explained by the observed inhibitory effect of IL-1? +3953T allele on the secretion of IL-1? under inflammatory circumstances.